Following in your father's footsteps: A note on the intergenerational transmission of income between twin fathers and their sons - Vikesh Amin; Petter Lundborg; Dan-Olof Rooth (Institute for the Study of Labor (IZA), 2011)
We provide the first twin-based estimates of the intergenerational transmission of income between fathers and sons. Using Swedish register data on the income of monozygotic twin fathers and their sons, we are able to control for unobserved endowments at the twin-pair level when estimating the intergenerational relationship. We find a cross-sectional intergenerational income elasticity of 0.276, while our twin-based intergenerational income elasticity is 0.12. This is close to the estimate of 0.10 found by Björklund et al. (2006) using an adoption design. This suggests that at most half of the income transmission can be given a causal interpretation.
urn:nbn:de:101:1-201110263271
Keywords: J0; J1; 330; twins; income; intergenerational transmission; intergenerational mobility; Einkommenselastizität; Generationenbeziehungen; Väter; Kinder; Schweden